HUBUNGAN STIMULASI DAN PENGETAHUAN ORANG TUA TERHADAP PERKEMBANGAN BAHASA PADA ANAK BALITA USIA 1-2,5 TAHUN DI PUSKESMAS I DENPASAR SELATAN - Ni Wayan Ari Adiputri (JOMIS (Journal of Midwifery Science), 2021)
Children's language skills are the most complex form of child development among other children's abilities, because of this, there are many children who experience language disorders or delays. The design of this study is a correlation study with a cross-sectional approach. This research has been conducted at Puskesmas I South Denpasar. The sample size is 40 people, using purposive sampling technique. Data were collected by direct observation with KPSP monitoring tools. The data analysis technique used is the Chi-Square test because the data are not normally distributed. This study aims to determine the relationship between parenting and language development in children 1-2.5 years. The results of this study found that there was no relationship between stimulation (p = 0.477) and parental knowledge (p = 0.385) with language development in toddlers aged 1-2.5 years. The results of this study are expected to be a reference for monitoring the growth and development of infants and toddlers, especially language development at Puskesmas I, South Denpasar.